1989
DOI: 10.1016/0020-7292(89)90849-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of copper T‐200 with Lippes loop as a contraceptive device

Abstract: A comparison has been made between Lippes loop and T Cu 200 intra-uterine contraceptive device with respect to their acceptability and effectiveness in a developing country. A total of 1054 patients were studied; 697 with Lippes loop and 357 with T Cu 200. The ages of the patients ranged between 14 and 44 years, with a peak age of 21-25 years for T Cu 200 and 26-30 for Lippes loop. The event rates were similar but T Cu 200 displayed lower expulsion rate, lower intermenstrual bleeding rate and a lower incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These changes have increased the efficiency of IUDs. 7,8 CONCLUSION A long-standing IUCD can lead to many problems starting from infertility to postmenopausal bleeding, pain abdomen, fever, malaise due to pelvic inflammatory disease, and actinomycosis. Timely removal of IUD is highly warranted to avoid the above complications.…”
Section: Discussionmentioning
confidence: 99%
“…These changes have increased the efficiency of IUDs. 7,8 CONCLUSION A long-standing IUCD can lead to many problems starting from infertility to postmenopausal bleeding, pain abdomen, fever, malaise due to pelvic inflammatory disease, and actinomycosis. Timely removal of IUD is highly warranted to avoid the above complications.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier IUD that was made of plastic materials has been replaced by new devices releasing copper or levonorgestrel. These modifications increased the already high efficiency [3,5]. The prospective cohort study was done in the US to analyze satisfaction and continuation of using different contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that long-acting reversible contraceptive methods are most effective and not user-dependent [2]. Many experts believe that IUD has highest continuation rates and the highest level of satisfaction amongst all the methods of contraception [2,3,5]. …”
Section: Discussionmentioning
confidence: 99%